MAGICAL REALISM IN IBTISAM AZEM’S THE BOOK OF DISAPPEARANCE - Intisar Rashid Khaleel , Zainab Abdullah Hussein , Awfa Hussein Al-Doory (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Magical realism is an inimitable literal movement which is linked with authors from the Latin American background. The world is grounded in the actual world, with fantastical factors considered normal in the world. Just like fairy tales, magical realism novels and short tales distort the line distinguishing truth and fantasy. The traits of magical realism are realistic settings containing supernatural elements. Most books have speaking objects and lifeless characters. Telepathy is also a frequent function in these stories. The authors of magical realism deliberately fail to provide an explanation for the magic in their words, which normalizes it making it appear like an everyday part of everyday life. An author makes use of magical realism to supply a critique to society and specifically the politics and moves of the elite. The style has expanded in reputation over the years. Therefore, this analysis pursuits to explain the magical realism in " The Book of Disappearance" by Ibtisam Azem. Following the characteristics of magic realism genre as a method of analysis is to achieve the aim of the paper.The paper starts with an introduction to the subject and the genre, the synopsis of the novel, the discussion and the analysis will be presented in the second part, then it ends with the conclusion that sums up the results of the analysis.